Модель быстродействующего электромагнитного привода для управляющего клапана системы питания теплового двигателя - Врублевский, Александр Николаевич; Григорьев, Александр Львович (НТУ "ХПИ", 2014)
Моделируется работа привода клапана электроуправляемой форсунки дизеля. Особенностью модели является учёт вихревых токов и магнитного гистерезиса (что связано с использованием в приводе новых магнитные материалов), а также волн деформации в упругих элементах привода (что вызвано его быстродействием). Предполагается использовать эту же модель для совершенствования пуско-отсечных клапанов системы питания ракетных двигателей.

The operation of a high-speed valve actuator in an electrically controlled injector of an automotive diesel engine is analyzed and its athematical model is built. The model allows taking into account eddy currents and magnetic hysteresis at the anchor, elastic vibrations of the valve stem and the multiplier under deformations, and oscillations of the coils of the actuator spring. It is shown that using magneto-dielectrics for the magnetic core and hard magnetic alloys for the anchor, as well as changing the scheme of electromagnet boosting provides the required performance of the valve. It is planned to apply the same principles to improve the launching valves of the supply system of a thruster.
Model-speed electromagnetic actuator for controlling stem-propane supply system of the heat engine
Keywords: электроуправляемые форсунки; электромагнитный привод; магнитодиэлектрики; управляющий клапан; вихревые потоки; магнитный поток; electrically controlled injector; electromagnetic actuator; magneto-dielectric; magnetic hysteresis; eddy current; magnetic flux